Grief through the Lens of Psychoanalysis: Freud, Jung, Horney, Klein, Lacan, and Kübler-Ross (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
The article analyzes grief from the perspective of six key psychoanalytic and psychological theorists —Freud, Jung, Horney, Klein, Lacan, and Elisabeth Kübler-Ross— presenting a conceptual review of different understandings of loss and its subjective implications. It concludes that grief is a symbolic and emotional process of inner transformation essential to mental health.
Keywords: Grief; Psychoanalysis; Freud; Jung; Kübler-Ross; Loss.